Oportunidades para el sector agropecuario y el carbono azul en América Latina y el Caribe en los mercados voluntarios de carbono - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The agricultural sector in Latin America and the Caribbean (LAC) holds great potential to attract private investment for climate action and resilience through the voluntary carbon market (VCM). These investments can accelerate the transition to highly resilient, carbon-rich, productive, and diverse agricultural production systems. Through these improvements, the agricultural sector in LAC can yield significant climate benefits. However, tapping into VCM opportunities requires overcoming several systemic challenges. Funding can support the shift from sprawling, often poorly managed livestock farms to productive, well-managed silvopastoral systems. Most agricultural production systems can increase carbon content by integrating on-farm tree planting with existing crop systems. Additionally, significant untapped emissions mitigation potential exists in rice production and coastal ecosystems in LAC, both of which offer important climate and biodiversity benefits. Regional LAC governments—particularly agricultural ministries—can create an enabling environment for VCM investment. Political leadership by agricultural ministers is key to unleashing the positive contributions of the VCM while ensuring the high integrity of market activities.